2012
DOI: 10.1080/1745039x.2012.683324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary sunflower oil and coconut oil on adipose tissue gene expression, fatty acid composition and serum lipid profile of grower pigs

Abstract: The present study was conducted to assess whether the partial replacement of feed energy by vegetable oils containing high medium-chain saturated fatty acids (MCFA) and n-6 polyunsaturated fatty acids (PUFA) would modify lipogenic gene expression and other parameter of fat metabolism in pigs. Eighteen pigs (17-19 kg body weight) received one of three experimental diets for 60 days (six animals per group): (i) Control diet; (ii) a diet with sunflower oil (SO) or (iii) a diet with coconut oil (CO). In diets SO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
(25 reference statements)
4
2
0
4
Order By: Relevance
“…A similar finding was observed by Clarke and Jump () who reported that dietary PUFA inhibits more hepatic de novo fatty acid synthesis than feeds containing saturated and monounsaturated fatty acids. These results are also consistent with Harihara Iyer et al () and Sandeep et al () who reported that FAS mRNA levels were lower when pigs were fed with sunflower‐ and coconut oil‐based feeds and cattle were fed corn oil, respectively, and these result indicated that n‐6 PUFA may reduce lipogenesis in porcine and bovine adipose tissue. Sanz et al () observed that addition of SO in broiler diet significantly reduced abdominal fat by preventing FAS activity in the liver and increasing CPT I and L3HOAD activity in the heart when compared to the diet with the inclusion of tallow.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A similar finding was observed by Clarke and Jump () who reported that dietary PUFA inhibits more hepatic de novo fatty acid synthesis than feeds containing saturated and monounsaturated fatty acids. These results are also consistent with Harihara Iyer et al () and Sandeep et al () who reported that FAS mRNA levels were lower when pigs were fed with sunflower‐ and coconut oil‐based feeds and cattle were fed corn oil, respectively, and these result indicated that n‐6 PUFA may reduce lipogenesis in porcine and bovine adipose tissue. Sanz et al () observed that addition of SO in broiler diet significantly reduced abdominal fat by preventing FAS activity in the liver and increasing CPT I and L3HOAD activity in the heart when compared to the diet with the inclusion of tallow.…”
Section: Resultssupporting
confidence: 90%
“…b). Similar findings were found by Harihara Iyer et al () and Kim et al () who detected a reduction of SCD mRNA levels in adipose tissues in pigs fed SO diet, suggesting that n‐6 PUFA may reduce lipogenesis in adipose tissues. Figure c represents a rather precipitous decrease in FAS gene expression with increasing levels of UFA sources of oil (SO).…”
Section: Resultssupporting
confidence: 88%
“…The situation was the opposite when feeding AM10 since this diet decreased the expression of the genes studied, a situation similar to that pointed out by Mohan et al (2012), who reported that the expression of the important lipogenic mediator SREBP1, can be affected by the type of diet, as it happened in the AM10 diet, where it is not overexpressed.…”
Section: Considerations Ofsupporting
confidence: 76%
“…ACP, ACACA and FASN to lipogenesis, and SREBP1 as a transcription factor and regulator of the expression of different lipogenic genes (Benitez et al, 2018;Fernandez et al,2017;Li et al, 2020;Mohan et al, 2012;. The change in diet can modify the proportion of lipids, to the point that pork meat can provide a health benefit to the consumer ).…”
Section: Materials Y Métodosmentioning
confidence: 99%
See 1 more Smart Citation